miR-30 Family miRNAs Mediate the Effect of Chronic Social Defeat Stress on Hippocampal Neurogenesis in Mouse Depression Model - Khandelwal, Nitin; Dey, Sandeep Kumar; Chakravarty, Sumana; Kumar, Arvind (Frontiers in Molecular Neuroscience, 2019)
Depression is a debilitating psychiatric disorder with a high rate of relapse and low rate of response to antidepressant treatment. However, there is a dearth of new drugs, attributed to our incomplete understanding of the molecular mechanisms involved in its etiopathology. Chronic stress appears to be one of the foremost underlying causes of depression. Using various animal models, efforts in the past decade has implicated epigenetic mechanisms in mediating the negative effects of chronic stressful events on the progression/manifestation of depression and other co-morbid neuropsychiatric disorders. However, non-coding RNAs, another layer of epigenetic regulation is relatively lesser studied in this context. Here, using the chronic social defeat stress (CSDS)-induced depression model, we aimed to uncover dysregulation in miRNA-mRNA networks in the neurogenic dentate gyrus (DG) region of male C57BL/6 mice. Among several dysregulated miRNAs, identified via miRNA arrays, the most striking finding was attenuated expression of miRNAs of the miR-30 family in stressed/defeated mice. To investigate miRNAs in the DG-resident neural stem/progenitor cells (NSCs/NPCs), we used the in vitro neurosphere culture, where proliferating NSCs/NPCs were subjected to differentiation. Among several differentially exprerssed miRNAs, we observed an upregulation of miR-30 miRNAs upon differentiation. To search for the gene targets of these miRNAs, we performed gene arrays followed by bioinformatics analysis, miRNA manipulations and luciferase assays. Our results suggest that miR-30 miRNAs mediate chronic stress-induced depression by altering hippocampal neurogenesis and neuroplasticity via controlling the epigenetic/transcription regulators such as Mll3 and Runx1 and cell signaling regulators like Socs3, Ppp3r1, Gpr125, and Nrp1.